Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Pegawai pada Balai Penjaminan Mutu Pendidikan (BPMP) DKI Jakarta - Saskia Kirana; Rony Edward Utama (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2025)
Human Resource Management (HRDM) has a strategic role in managing, directing, and developing employee potential to achieve organizational goals effectively and efficiently. One of the indicators of MSDM's success is the achievement of optimal employee performance. Employee performance is a crucial aspect in ensuring the effectiveness and operational efficiency of the organization, especially in government agencies such as the Jakarta Education Quality Assurance Center (BPMP), which has a mandate to guarantee and improve the quality of education in its area. This study aims to find out the extent of the influence of Leadership Style and Work Motivation on the Performance of BPMP DKI Jakarta Employees. This study uses a quantitative approach with an associative method, which aims to examine the relationship between two independent variables, namely Leadership Style and Work Motivation, to the dependent variable, namely Employee Performance. The data collection technique was carried out through the distribution of questionnaires to 57 respondents determined using the Slovin formula from a total population of 132 employees. The data obtained were analyzed using multiple linear regression with a series of tests such as validity, reliability, classical assumptions (normality, multicollinearity, and heteroscedasticity tests), and hypothesis tests (t-tests and F tests). The results of the study show that both Leadership Style and Work Motivation have a positive and significant influence on Employee Performance partially. This means that improvements in leadership and work motivation directly have an impact on increasing productivity and the quality of employee performance. These findings indicate that the management of BPMP DKI Jakarta needs to pay greater attention to the development of effective leadership and the creation of a work environment that is able to motivate employees. This research is expected to be a reference for policy makers in designing human resource management strategies that are oriented towards improving performance in a sustainable manner.